GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 21006 species occurrences available in GBIF matching the query: TaxonKey: Carlina acaulis L. HasCoordinate: true HasGeospatialIssue: false. The dataset includes 21006 records from 109 constituent datasets: 2 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 8 records from InsectScale2008FlowerCover. 6 records from University of Vienna, Institute for Botany - Herbarium WU. 1 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 15 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 14 records from Artdata. 3 records from OHN. 156 records from Données ONF Faune-Flore-Fonge. 1 records from Australia's Virtual Herbarium. 370 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 38 records from iNaturalist Research-grade Observations. 8 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 1 records from Artenvielfalt Kreis Gießen. 10 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 14 records from Thistle Heads and Ermerged Insects. 1 records from Trockenrasen bei Dörndorf. 1 records from Natur-Erlebnis-Kindergarten Waldkirchen/Erzgebirge. 1 records from Weidewirtschaft. 1 records from Naturschutzgebiet Kochertgraben. 1 records from FFH-Gebiet "Calwer Heckengäu". 4 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 1 records from Aktion der Klasse H2 in Simmelsberg. 2806 records from Occurrence Data of Vascular Plants collected or compiled for the Flora of Bavaria. 2 records from flower availability 2008 Alb-korrigiert. 448 records from naturgucker. 2 records from flower visitor interactions 2008. 1 records from Biotope in Rheine - Aktion 350. 1 records from Artenvielfalt vor unserer Kita-Haustür. 10724 records from INPN - Données flore des CBN agrégées par la FCBN. 3 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 1 records from CeDoc de Biodiversitat Vegetal: BCN-Seeds. 5 records from Tiroler Landesmuseum Ferdinandeum. 2 records from The Fungal Collection at the Botanische Staatssammlung München. 482 records from IBF Monitoring of Vascular Plants. 1 records from Natural History Museum (London) Collection Specimens. 20 records from Catálogo Florístico Histórico de Navarra. Gobierno de Navarra. 11 records from Natural History Museum, Vienna - Herbarium W. 20 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 2 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 3 records from Universidad de Barcelona. Grup dInvestigació Geobotánica i Cartografia de la Vegetació. 1 records from Universität Salzburg. 3 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 6 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 2 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 2 records from CeDoc de Biodiversitat Vegetal: BCN-Cormophyta. 4 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 1 records from Jardín Botánico de Córdoba: Herbarium COA. 7 records from Aranzadi Zientzi Elkartea. 1 records from CIBIO, Alicante:ABH-GBIF. 3 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 8 records from Institut Botanic de Barcelona, BC. 1 records from DAV UC Davis Center for Plant Diversity. 2 records from Herbarium Berolinense. 185 records from Observations du Conservatoire botanique national du Bassin parisien.. 25 records from Biologiezentrum Linz. 1 records from Institut Botanic de Barcelona, BC-Histórico. 9 records from inatura - Erlebnis Naturschau Dornbirn. 1 records from EURISCO, The European Genetic Resources Search Catalogue. 12 records from Thistles species and abundance. 133 records from Biodiversitätsdatenbank des Landes Salzburg. 136 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 1 records from Danielsberg (Mölltal, Kärnten). 1 records from Sandhofen. 1 records from Schlichemquelle (Tieringen/Meßstetten). 1 records from GEO Hauptveranstaltung Tirol (Innsbruck). 1 records from Schule Sulzbach (Oberegg). 1 records from NSG Karwendel. 1 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 1 records from Neckartalsüdhang (Horb). 1 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 1 records from Trockenrasen und Buchenwald in der Umgebung der Jugendherberge Bad Blankenburg. 1 records from Gurgltal (Tarrenz). 1 records from 20 Jahre Naturschutzgebiet Dreienberg. 1 records from Gemeindegebiet Weikendorf (Marchfeld). 1 records from Streuobstwiese Kugelberg (Ulm). 1 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 1 records from Arteninventar rund um den Rannahof. 44 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 1 records from Perchtoldsdorfer Heide. 1 records from Biosphärenreservat Münsinger Alb. 1 records from Flora und Fauna in unserer Kita. 1 records from Kohlstattbrunnental. 5 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 1 records from EDIT - ATBI in Gemer area (Slovakia). 1 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 1 records from VFD-BW, Schwäbische Alb: Pferdeweiden Zainingen. 11 records from Herbarium Senckenbergianum (FR). 3 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 11 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 2 records from Floral visits on plants, InsectScale 2008. 954 records from FloraCAT: Banco de datos de los cormófitos de Cataluña. 30 records from Flora d'Andorra. 32 records from National System of Protected Areas in Poland - Plants. 99 records from vegetation releves on grassland gridplots 2007-2009. 109 records from vegetation releves on grassland gridplots in 2007. 2 records from pflanzendiversitaet_2008_sch_alb_hai_aktualisiert. 2 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 58 records from Carnet en Ligne. 2 records from University of British Columbia Botanical Garden Collections (UBCBG). 10 records from Thistles damage. 156 records from Données ONF Faune-Flore-FOnge. 821 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 3 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 2 records from Plants, herbivores and their natural enemies along a grassland management gradient 2008. 4 records from Thistles and numbers of observed invertebrates, fungi and damage types. 1 records from Vascular Plant Herbarium, Oslo (O). 2736 records from Flora von Deutschland (Phanerogamen). 136 records from Flora of the Stołowe Mts.. 16 records from Vegetation releves in 150 grassland EPs in 2008. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences